2016
DOI: 10.1111/vcp.12435
|View full text |Cite
|
Sign up to set email alerts
|

Extreme lymphocytosis with myelomonocytic morphology in a horse with diffuse large B‐cell lymphoma

Abstract: An 11-year-old, 443-kg Haflinger mare was presented to the North Carolina State University Veterinary Teaching Hospital with a 2-week history of lethargy and a 3-day duration of anorexia, pyrexia, tachycardia, and ventral edema. Severe pitting edema, peripheral lymphadenopathy, and a caudal abdominal mass were noted on physical examination. An extreme leukocytosis (154.3 × 10 /μL) and microscopic hematologic findings suggestive of myelomonocytic leukemia were observed. Serum protein electrophoresis revealed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…), and has recently been described for lymphoma in horses (Meichner et al . ). Briefly, PARR testing assesses DNA from cells to ascertain if they come from the same cell line, termed monoclonal (typically neoplastic), or from different cell lines, termed polyclonal (typically reactive) (Avery ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…), and has recently been described for lymphoma in horses (Meichner et al . ). Briefly, PARR testing assesses DNA from cells to ascertain if they come from the same cell line, termed monoclonal (typically neoplastic), or from different cell lines, termed polyclonal (typically reactive) (Avery ).…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, PARR has been used to successfully identify diffuse intermediate to large B cell lymphoma with a robust haematogenous phase (TCRLBCL) in both blood and infiltrative tissue from a horse with multicentric disease (Meichner et al . ). To the authors’ knowledge, this is the first documented use of PARR in equine solitary extranodal lymphoma.…”
Section: Discussionmentioning
confidence: 97%
“…), and it has also been used to aid the diagnosis of a diffuse large cell lymphoma (Meichner et al . ) and for characterisation of B cell neoplasms (Badial et al . ).…”
mentioning
confidence: 99%
“…A significant difference between the case series was the presence of left-shifted neutrophils with toxic change in 1 study, which suggested bone marrow damage; however, this finding was not supported in the current study, as toxicity was rarely noted, a finding that agrees with other reports of equine leukemia. [1][2][3][4][5][6] The rapid release of maturing neutrophils that results in toxicity is typically related to infectious or toxic insults to the bone marrow, but under some conditions, leukemia (especially with severe neutropenia) may result in a similar finding.…”
mentioning
confidence: 99%
“…The 1 lymphoid leukemic case that was unclassified as either B or T could have been further evaluated by molecular analysis to determine which population was clonal and which was reactive, as previously demonstrated in a case report. 3,5 Note that a panel of B and T immunomarkers is better than single lineagespecific markers. Furthermore, some cell types require >1 antibody for identification; for example, CD20 and CD79a are often used concurrently to identify B-cell lineage.…”
mentioning
confidence: 99%